NATIONAL-PROGRESSIVE MOVEMENT: VIEWS OF JADIDS ON STATEHOOD - Mamajonova Gulnoza Karimovna (International Journal of Innovations in Engineering Research and Technology, 2021)
This article deals reformist movement of Turkestan late XIX-XX centuries and complex, historically multifaceted way of development.